Bed rest or mobilization after rt‐PA? A case‐crossover study of factors influencing clinical decision making in stroke services. Issue 3 (13th October 2011) - Ha, Jason; Churilov, Leonid; Linden, Thomas; Bernhardt, Julie
<x xml:space="preserve">Abstract</x> Background Acute stroke management is a dynamic field. Treatment with recombinant tissue plasminogen activator is standard care in Australia, but there are no evidence‐based practice guidelines about first out of bed activity (mobilization) after recombinant tissue plasminogen activator. Aims To identify factors influencing clinicians' decisions to delay or allow mobilization. Methods Case‐crossover design. Using hypothetical case vignettes, we explored the factors that clinicians consider when deciding to first mobilize a patient after recombinant tissue plasminogen activator. Acute stroke physicians and nurses from Australian hospitals known to treat with recombinant tissue plasminogen activator participated. Information about hospital recombinant tissue plasminogen activator protocols and perceived benefits and harms of mobilization after recombinant tissue plasminogen activator were also captured. Results Fifty‐four clinicians, 52% senior nurses, and 48% senior physicians from all states of Australia participated. Of the factors influencing decisions about mobilization after recombinant tissue plasminogen activator, neurological decline (0·29; confidence interval 0·12, 0·46; P = 0·001), neurological decline with symptomatic intracerebral hemorrhage (0·41; confidence interval 0·24, 0·59; P < 0·0001), infection of uncertain cause (0·32; confidence interval 0·14, 0·50; P = 0·001), severe chest infection (0·35; confidence interval 0·16, 0·53; P = 0·0004), severe stroke (0·29; confidence interval 0·12, 0·46; P = 0·001), drowsiness (0·47; confidence interval 0·29, 0·63; P < 0·0001), and confusion (0·31; confidence interval 0·15, 0·47; P = 0·0001) significantly influenced decisions. Falls risk was a common concern (85%). Conclusion Growing interest in development of clear protocols that guide first mobilization after recombinant tissue plasminogen activator prompted this study. We have identified factors that may influence decisions about when to allow patients to mobilize after recombinant tissue plasminogen activator. These, combined with emerging evidence of risks and benefits of early mobilization, should help protocol development in the future.